2021
DOI: 10.7181/acfs.2021.00444
|View full text |Cite
|
Sign up to set email alerts
|

Facial reanimation using the hypoglossal nerve and ansa cervicalis: a short-term retrospective analysis of surgical outcomes

Abstract: Background: Transferring the hypoglossal nerve to the facial nerve using an end-to-end method is very effective for improving facial motor function. However, this technique may result in hemitongue atrophy. The ansa cervicalis, which arises from the cervical plexus, is also used for facial reanimation. We retrospectively reviewed cases where facial reanimation was performed using the ansa cervicalis to overcome the shortcomings of existing techniques of hypoglossal nerve transfer.Methods: The records of 15 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The procedure achieved reanimation of the facial nerve with a major side effect of tongue dysfunction due to the entire resection of the hypoglossal nerve [ 25 ]. Thus, researchers put forward a modified technique that an anastomosis was performed between the proximal stump of ansa cervicalis and the distal stump of the hypoglossal nerve after classical HFA to avoid morbidity related to tongue function [ 16 , 26 ]. However, there was an argument about the effectiveness of modified HFA in hemiglossal function preservation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The procedure achieved reanimation of the facial nerve with a major side effect of tongue dysfunction due to the entire resection of the hypoglossal nerve [ 25 ]. Thus, researchers put forward a modified technique that an anastomosis was performed between the proximal stump of ansa cervicalis and the distal stump of the hypoglossal nerve after classical HFA to avoid morbidity related to tongue function [ 16 , 26 ]. However, there was an argument about the effectiveness of modified HFA in hemiglossal function preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Hammerschlag et al [ 27 ] also denied the usefulness of ansa cervicalis-hypoglossal distal stump anastomosis in tongue function protection. However, a recent study by Won Young Koo et al [ 16 ] showed that facial reanimation with hypoglossal nerve transfer, combined with hypoglossal nerve neurotization using the ansa cervicalis for complete facial palsy patients, might enable favorable facial restoration and reduce the incidence of tongue dysfunction. The Department of Neurosurgery at Xinhua Hospital believed that the advancement in surgical skills in recent years may improve the effectiveness of this modified HFA in hemiglossal function preservation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the high motor neuron content of the masseter nerve allows for superior muscle mobility compared to facial nerve cross-transplantation. In general, splitting the hypoglossal nerve can reduce donor site defects such as dysarthria and masticatory disorders [ 23 ]. Biofeedback training after nerve crossover can aid in the control of voluntary facial muscle movements and reduce synkinesis.…”
Section: Treatment Of Facial Nerve Damagementioning
confidence: 99%